2016
DOI: 10.4082/kjfm.2016.37.6.346
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Predictive Index for Osteoporosis as a Clinical Tool to Identify the Risk of Osteoporosis in Korean Men by Using the Korea National Health and Nutrition Examination Survey Data

Abstract: BackgroundWe previously proposed the Predictive Index for Osteoporosis as a new index to identify men who require bone mineral density measurement. However, the previous study had limitations such as a single-center design and small sample size. Here, we evaluated the usefulness of the Predictive Index for Osteoporosis using the nationally representative data of the Korea National Health and Nutrition Examination Survey.MethodsParticipants underwent bone mineral density measurements via dual energy X-ray absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…However, the sensitivity and specificity of OSTA, 71.9% and 64.0%, respectively, and the sensitivity and specificity of PIO, 67.6% and 72.7%, respectively, was higher than the results of our study. The difference in the results of our study may be because of the differences in the population characteristics since our study included both men and women, and the prevalence of osteoporosis in our study was found to be higher at 40.7% as compared to the above study which was at 4.9% [ 19 ].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…However, the sensitivity and specificity of OSTA, 71.9% and 64.0%, respectively, and the sensitivity and specificity of PIO, 67.6% and 72.7%, respectively, was higher than the results of our study. The difference in the results of our study may be because of the differences in the population characteristics since our study included both men and women, and the prevalence of osteoporosis in our study was found to be higher at 40.7% as compared to the above study which was at 4.9% [ 19 ].…”
Section: Discussionmentioning
confidence: 72%
“…Assessment of smoking status for the prediction of osteoporosis was supported by recent research results such as in the Framingham study wherein current smokers exhibited greater bone loss than former or never smokers [ 17 ]. Although in a similar study conducted by Moon et al, their results also showed that there was no statistically significant difference between the 2 ROC graphs of OSTA and PIO [ 19 ]. However, the sensitivity and specificity of OSTA, 71.9% and 64.0%, respectively, and the sensitivity and specificity of PIO, 67.6% and 72.7%, respectively, was higher than the results of our study.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Individuals with osteoporosis have a higher risk for fragility fractures due to reduced bone density, and increased risk for resulting complications and mortality rates. (2) Fragility fracture refers to a non-traumatic fracture and, according to the World Health Organization (WHO), is de ned as a fracture caused by a fall from a level below one's height, including fracture(s) caused by impact that do not cause fracture(s) in normal bones, and even when that impact is not recognized. (3) In Korea, women > 50 (59.5%) are more likely to experience fragility fractures in their lifetime than men > 50 (23.8%) years of age.…”
Section: (Knhanes Iv) Backgroundmentioning
confidence: 99%